Foreign Policy of Nepal: Perception of International Relations Committee Members, GoN (2023 to 2025) - Kanwar, Kalidas (Dristikon: A Multidisciplinary Journal, 2026)
The research study analyzed the understanding of the international relations committee members, to measure the perception on Nepalese foreign policy in contemporary political development of Nepal. Thus, the research issue concerns the question of what is or should be regarded as acceptable perception in a discipline for the smooth growth and development of foreign policy of Nepal. The research is dais on quantitative research methods that reflect the understanding of the perception of the international relations committee members regarding political awareness in respect to international relations, Government of Nepal (GoN) based on foreign policy and its execution. In this regard, primary data has been collected, analyzed and interpreted using SPSS. The purpose of this research is to explore and analyze Nepal’s diplomatic positing within the geopolitical and international political environment, particularly in relation to its foreign policy. Understanding these dynamics is fundamental for acquisitive how Nepal navigates its relationships and influences in a complex global milieu. The research relies on six variables of international relations and foreign policy such as Nepal’s position in IR based on foreign policy, national interests, international political economy, socio-cultural relations and international organizations. The research philosophy is under pragmatism followed by the inductive research approach. The methodological choice is based on quantitative and the survey research strategy is applied. Thus, the entire research as based on the low politics or soft power of IR and foreign policy mechanism.